Facing a dilemma: Cooperative behavior and beauty - Donja Darai; Silvia Grätz (University of Zurich, Department of Economics, 2012)
This paper investigates the influence of physical attractiveness on cooperative behavior. We survey data from 211 episodes of a television game show and combine it with independent facial attractiveness ratings of the show's contestants. The final of the show represents a simultaneous one-shot modified prisoner's dilemma. Our results show that facially attractive contestants provoke cooperative behavior from their counterparts, but attractive contestants themselves do not behave differently from unattractive ones. This preferential treatment or beauty premium rewards attractive contestants with substantially higher monetary gains of up to 2 153. This finding applies to both sexes. But, the attractiveness effect is limited to mixed-gender interactions. Contestants are only more cooperative when facing an attractive fellow player of the opposite sex. Attractiveness also has no effect in group-decisions made by the contestants prior to the prisoner's dilemma. Therefore people seem to show a preference to cooperate with someone towards whom they are personally attracted; and this preference reaches full effect when people lack other information on which to base their decision.
Keywords: C71; D83; Z13; 330; beauty premium; cooperation; prisoner's dilemma; Gefangenendilemma; Kooperatives Spiel; Theorie